Pengawasan Pemerintah Daerah terhadap Usaha Pertambangan Galian C di Kabupaten Ngada - Matius Ade Krispian Soba Nono; I Ketut Kasta Arya Wijaya; Luh Putu Suryani (Jurnal Interpretasi Hukum, 2020)
Mining of rock minerals in the sandstone and gravel type is a mining commodity owned by the people of Naru village which requires supervision by the local government. Unfortunately, there are still problems in monitoring mining activities of excavation C, which are not in accordance with mining principles. This study aims to determine the role of the local government in the supervision of mining excavation C as well as the factors that influence the existence of the C mining activities in Ngada Regency. This research uses an empirical legal method, which is a study examining problems according to facts that take place in the field. The results show that the Ngada Regency Government no longer has the authority to supervise the mining since it has been taken over by the Provincial Government, starting with the issuance of Law No. 23 of 2014 concerning the Regional Government. The factor hampering the mining supervision and licensing process is that it is difficult for miners and mining companies to apply for permits whereas business owners are obliged to obtain mining permits from the Provincial Government. Given the great distance, this has been one of the factors causing many illegal mining activities to occur in Ngad Regency.